1993
DOI: 10.1113/jphysiol.1993.sp019956
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of injections of kainic acid into the prepositus and the vestibular nuclei of the cat.

Abstract: SUMMARY1. In order adequately to control eye movements, oculomotoneurones have to be supplied with both an eye-velocity signal and an eye-position signal. However, all the command signals of the oculomotor system are velocity signals. Nowadays, there is general agreement about the existence of a brainstem network that would convert velocity command-signals into an eye-position signal. This circuit, because of its function, is called the oculomotor neural integrator. The most obvious symptom of its eventual fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Vestibular nystagmus (fast unidirectional drift) is often caused by unilateral damage to the vestibular nerve or semicircular canals. Pharmacological inactivation of the MVN or PH can produce centripetal or unidirectional ocular drift (9,(14)(15)(16)(17)(18)(19). Some patients with cerebellar disease suffer from centrifugal ocular drift away from a null position, suggesting a memory state space with a saddle point, as shown in Fig.…”
Section: Perturbations Of Dynamicsmentioning
confidence: 95%
See 2 more Smart Citations
“…Vestibular nystagmus (fast unidirectional drift) is often caused by unilateral damage to the vestibular nerve or semicircular canals. Pharmacological inactivation of the MVN or PH can produce centripetal or unidirectional ocular drift (9,(14)(15)(16)(17)(18)(19). Some patients with cerebellar disease suffer from centrifugal ocular drift away from a null position, suggesting a memory state space with a saddle point, as shown in Fig.…”
Section: Perturbations Of Dynamicsmentioning
confidence: 95%
“…Stimulation of the MVN or PH causes persistent changes in eye position (9)(10)(11). Electrolytic lesion (12,13) or pharmacological inactivation (9,(14)(15)(16)(17)(18)(19) of these areas causes the disorder gazeevoked nystagmus. Such experimental results indicate that these premotor neurons are part of the network that stores the memory of eye position.…”
Section: The Memory Of Eye Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the target, velocity imbalance and/or integration deficit will occur, leading to well characterized abnormal eye movements (C annon and Robinson, 1987;Godaux et al, 1993;Mettens et al, 1994;Pastor et al, 1994;Godaux and Cheron, 1996), which are schematically represented in Figure 1. Each PH nucleus simultaneously receives excitatory and inhibitory signals from the contralateral and ipsilateral M V nuclei, respectively (Baker and Berthoz, 1975).…”
Section: Abstract: Eye Movements; Nitrergic Neurons; Nitric Oxide; Omentioning
confidence: 99%
“…The nucleus prepositus hypoglossi (NPH) was previously shown to function as the neural integrator for horizontal eye movements (Cannon and Robinson 1987;Godaux et al 1993;McFarland and Fuchs 1992). A number of studies showed that the mesencephalic interstitial nucleus of Cajal (INC) is the neural integrator for vertical and torsional components of eye movements (Crawford 1994;Crawford and Vilis 1993;Fukushima 1987;Fukushima et al 1990;Helmchen et al 1998;King et al 1981;Ranalli et al 1988).…”
Section: Introductionmentioning
confidence: 99%